Board game in the study of exoplanets (Research, Society and Development, 2022)
Guided by conceptual aspects of Vygotsky's Learning Theory, we built a table top type didactic game to analyze the teaching and learning process concerning the study of exoplanets. This educational product was made in a way that could make the teaching of Physics more attractive, dynamic and interactive, we sought to promote an innovative learning process about Exoplanets. We carried out the research by applying the game, as an educational product, in a sample of 66 students from the school. Profª. Salomé Carvalho (9th grade students - Elementary School), belonging to the municipal public network of Marabá-PA. In general terms, we highlight the work developed with previous knowledge presented by students about planets, as well as discussion and presentation in a playful, dynamic and interactive way of new knowledge about extrasolar planets, their characteristics and detection methods. We also emphasize that the didactic game developed and applied presented potential applicability in other educational contexts, approaching different themes in other areas of knowledge.